Significados semióticos percebidos e indícios estatísticos de inclusões sociais de egressos de projeto esportivo de caráter social de educação olímpica - Camargo, Leonardo Perovano (2022)
Throughout history, sport has been used as a means or tool for education in values, with the reiterated discourse that it may be capable of proposing positive transformations in the lives of children and adolescents. In the contemporary world, a series of social intervention initiatives use sport as a tool to achieve social inclusion, crime prevention, among other social objectives. Scheila Antunes (2018) defined these social intervention initiatives as “Social Sports Projects” (PECS). According to this researcher, PECS can be defined as those enterprises of non-specific social assistance organizations, which offer one or more sports as the main action strategy to transform a portion of reality, reducing or eliminating a deficit, or solving a social problem.